Is it possible that logged-over areas can recover naturally: the case of logged-over areas in South Kalimantan. Issue 1 (July 2021) - Qirom, M A; Andriani, S; Halwany, W; Lestari, F
Abstract: Logging causes a decline in the quality of stands in all forest types. However, these forests can recover naturally. This study aims to measure the ability to recover logged-over areas based on the species composition and above-ground biomass. This research was conducted by logged-over forest in 1987, of lowland forest type in the Kintap Research Forest, South Kalimantan. The research was carried out by making a measurement plot on three types of land with the main road's distance as a differentiating factor. Each type of measurement plot measuring 1 hectare is divided into five replications with 20 m × 100 m. The measurement parameters are the diversity of species and above-ground biomass estimated by the allometric model. The results showed that the distance difference did not affect the species composition and the potential for above-ground ground biomass. The species composition is indicated by the diversity index, evenness index, and dominance index, including above-ground biomass. Overall, more than 100 tree species present after felling and an evenness index of higher than 0.75, indicating that the community is stable with high species diversity and low dominance. This indicates that logged-over areas can recover but that recovery requires adequate regeneration after logging. The implication is that logging must leave enough standing stands. This condition will encourage natural regeneration or succession in logged-over forests.